Estimation of triboelectric properties of high-speed steels - Anatoly A. Ryzhkin; Evgeny V. Fominov; Yury A. Torop (Advanced Engineering Research, 2017)
Introduction. The paper is devoted to forecasting the operational properties of the existing and newly developed high speed steels depending on their chemical composition by the investigation of thermodynamic processes in the friction zone under cutting, and by receiving analytical dependences for evaluating friction and wear characteristics. The work objective is the prediction of wear resistance of high speed steels on the base of the structural sensitive parameters of the absolute or relative thermo-EMF and entropy of the material which can be calculated by the additivity rule at the known chemical composition. Materials and Methods . The theoretical relationship between the change in entropy of steels and their thermo-EMF is obtained. According to it, a smaller value of the absolute thermo-EMF corresponds to a larger value of the material entropy. This theoretical relationship is experimentally tested on various compositions of high speed steels. Research Results. To determine the relationship between entropy as a thermoelectric characteristic of high speed steels and their wear resistance, experimental tests on friction for the cylindrical samples of high speed steels of different types, and study on the wear properties of drills under steels machining are carried out. Measurements of relative thermo-EMF of these samples are performed; and their absolute values are calculated. The results of these tests show maximum wear resistance of high-speed steels having high values of entropy and low values of the absolute (relative) thermo-EMF. Discussion and Conclusions . The relationship between the wear resistance parameters of high speed steels and their structurally-sensitive characteristics at the micro-level - entropy and absolute thermo-EMF, is established. To reduce wear during friction and cutting, it is necessary to apply the types of high speed steels with maximal entropy and minimal thermo-EMF. Entropy, which with ease can be calculated on the known chemical composition of the material, can be used to assess the operating properties and to predict the wear resistance of both existing and newly developed compositions of high speed steels.